performance evaluation of half warm asphalt mixture prepared with natural and nano synthetic zeolite, chemical additives and polymers - hussein Mohamed; Ahmed Elsayed; Mohamed Abd el-latif; Abdelzaher Mostafa (JES: Journal of Engineering Sciences)
AbstractThis study evaluates the performance of Half Warm Mix Asphalt (HWMA) prepared with natural and nano synthetic zeolite, chemical additives, and polymers, aiming to develop an environmentally friendly alternative to conventional Hot Mix Asphalt (HMA). HWMA provides significant advantages, including reduced production temperatures and lower energy consumption, leading to decreased greenhouse gas emissions and improved worker safety. The research addresses the current gap in comparative analyses between HWMA and HMA by conducting comprehensive tests, including indirect tensile strength (ITS), loss of stability, and scanning electron microscope (SEM). The results demonstrated that HWMA modified with 10% synthetic zeolite, 5% epoxy, and 10% stearic acid achieved higher ITS values and reduced moisture susceptibility compared to conventional HMA. Notably, the inclusion of stearic acid at 90°C enhanced stability, resulting in a 9% reduction in stability loss when compared to the control sample. SEM analyses confirmed structural improvements and chemical interactions that contributed to enhanced performance. These findings highlight HWMA's potential as a sustainable and high-performance alternative to HMA without compromising mechanical properties.